2011
DOI: 10.19030/iber.v7i8.3283
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment Of The Stock Market And Exchange Rate Dynamics In Industrialized And Emerging Markets

Abstract: This paper adopts an Exponentional General

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 41 publications
2
29
1
1
Order By: Relevance
“…The unidirectional transmission of volatility between equity and currency market has been reported by following studies (Adjasi et al 2008;Antonakakis 2012;Beer and Hebein 2011;Chkili and Nguyen 2014;Ebrahim 2000;Fedorova and Saleem 2009;Kanas 2000;Kang and Yoon 2013;O'Donnell and Morales 2009;Okpara and Odionye 2012;Yang and Doong 2004;Yang and Chang 2008). Ebrahim (2000) empirically examined the flow of volatility of exchange rate on the developed equity markets.…”
Section: Review Of Literaturementioning
confidence: 94%
See 4 more Smart Citations
“…The unidirectional transmission of volatility between equity and currency market has been reported by following studies (Adjasi et al 2008;Antonakakis 2012;Beer and Hebein 2011;Chkili and Nguyen 2014;Ebrahim 2000;Fedorova and Saleem 2009;Kanas 2000;Kang and Yoon 2013;O'Donnell and Morales 2009;Okpara and Odionye 2012;Yang and Doong 2004;Yang and Chang 2008). Ebrahim (2000) empirically examined the flow of volatility of exchange rate on the developed equity markets.…”
Section: Review Of Literaturementioning
confidence: 94%
“…In this aspect, this study will be a novel contribution in reference to Sri Lanka. In context of China, Hong Kong, India and Japan, we have found many studies but with mixture of results like (Chkili 2012) and (Beer and Hebein 2011) reported contrasting results in case of Hong Kong. Similarly, (Mishra et al 2007) and (Beer and Hebein, 2011) found different results for India.…”
mentioning
confidence: 87%
See 3 more Smart Citations